Data‐Driven Two‐Level Performance Evaluation of Eddy‐Current Tuned Mass Damper for Building Structures Using Shaking Table and Field Testing. (26th May 2018) - Lu, Xilin; Zhang, Qi; Wu, Weichao; Shan, Jiazeng
Abstract: A computational framework with a two‐level performance evaluation is proposed for the tuned mass damper (TMD)‐structure system and is implemented for a new eddy‐current (EC) TMD in a data‐driven manner by incorporating the measurements from a shaking table test and real‐world field tests. The first level of evaluation corresponds to the data analysis with classical performance indices, whereas the second level focuses on the energy dissipation and exchange behavior in the time domain. Accordingly, two key steps of physical modeling and unmeasured response estimation are sequentially presented, and the steps adopt two types of energy balance formulations and state–space descriptions for the primary structure and the TMD, respectively. In the case of shaking table test, the momentary and cumulative behavior of energy dissipation and exchange at the second level is systematically revealed, and several key issues are identified for explaining the observed performance variation and excitation‐sensitivity. In the case of field test, the damping and control performance of the EC‐TMD at the real‐world scale is investigated with informative results using the first level evaluation.